Pentamidine niosomes thwart S100B effects in human colon carcinoma biopsies favouring wtp53 rescue - Seguella, Luisa (J Cell Mol Med, 2020)
S100B protein bridges chronic mucosal inflammation and colorectal cancer given its ability to activate NF‐kappaB transcription via RAGE signalling and sequestrate pro‐apoptotic wtp53. Being an S100B inhibitor, pentamidine antagonizes S100B‐wtp53 interaction, restoring wtp53‐mediated pro‐apoptotic control in cancer cells in several types of tumours. The expression of S100B, pro‐inflammatory molecules and wtp53 protein was evaluated in human biopsies deriving from controls, ulcerative colitis and colon cancer patients at baseline (a) and (b) following S100B targeting with niosomal PENtamidine VEhiculation (PENVE), to maximize drug permeabilization in the tissue. Cultured biopsies underwent immunoblot, EMSA, ELISA and biochemical assays for S100B and related pro‐inflammatory/pro‐apoptotic proteins. Exogenous S100B (0.005‐5 μmol/L) alone, or in the presence of PENVE (0.005‐5 μmol/L), was tested in control biopsies while PENVE (5 μmol/L) was evaluated on control, peritumoral, ulcerative colitis and colon cancer biopsies. Our data show that S100B level progressively increases in control, peritumoral, ulcerative colitis and colon cancer enabling a pro‐inflammatory/angiogenic and antiapoptotic environment, featured by iNOS, VEGF and IL‐6 up‐regulation and wtp53 and Bax inhibition. PENVE inhibited S100B activity, reducing its capability to activate RAGE/phosphor‐p38 MAPK/NF‐kappaB and favouring its disengagement with wtp53. PENVE blocks S100B activity and rescues wtp53 expression determining pro‐apoptotic control in colon cancer, suggesting pentamidine as a potential anticancer drug.